Milletlerarası Tahkimde Hakemin Reddi Sebebi Olarak Hakemin Tarafsızlığını ve Bağımsızlığını Ortadan Kaldıran Haller - (:unkn) unknown (My University, 2015)
Alternatif bir uyuşmazlık çözüm yöntemi olan milletlerarası tah- kim yargılaması sürecinde hakemler taraflardan bağımsız ve yargılama sırasında tarafsız olmalıdırlar. Tarafsızlık ve bağımsızlık yükümlülükle- rinin ihlali hakemin reddi sebebidir. Taraflar tarafsızlıkları ve bağımsız- lıkları hakkında haklı şüpheye sahip oldukları hakemi reddedebilirler. Hakemin reddi uluslararası tahkime ilişkin bütün düzenlemelerde bazı küçük farklılıklarla yer almaktadır. Bununla birlikte somut olarak hangi hallerde hakemin reddedilebileceği bu düzenlemelerde yer almamıştır. Red talebine konu olan her bir olayın özellikleri dikkate alınarak ha- kemin reddi hakkında karar verilmesi gerekmektedir. Bu çalışma han- gi hallerde hakemin tarafsızlık ve bağımsızlık yükümlülüklerinin ihlali nedeniyle reddedilebileceği ve bunun usulünü ele almaktadır.

Arbitrators should be independent from the parties and impar- tial during arbitration trial which is an alternative dispute settlement method. The breach of obligations to be impartial and independent is a reason for challenge of an arbitrator. The parties can challenge an arbitrator whom they have justifiable doubts about his impartiality and independence. The challenge of arbitrators exists in all regulations relating to international arbitration with small differences. However, in which situations can the parties challenge an arbitrator does not exist in these regulations. The decision on challenge of an arbitrator should be given through considering particularities of each situation that is the subject of challenge. This work discusses in which situations an arbitrator can be challenged due to the breach of obligations to be impartial and independent and the procedure of this challenge. Keywords: international arbitration, challenge of arbitrators, impar-
Keywords: Hukuk